Implementation of the ERAS (Enhanced Recovery After Surgery) protocol for colorectal cancer surgery in the Piemonte Region with an Audit and Feedback approach: study protocol for a stepped wedge cluster randomised trial: a study of the EASY-NET project. Issue 6 (3rd June 2021) - Pagano, Eva; Pellegrino, Luca; Rinaldi, Federica; Palazzo, Valentina; Donati, Danilo; Meineri, Maurizio; Palmisano, Sarah; Rolfo, Monica; Bachini, Ilaria; Bertetto, Oscar; Borghi, Felice; Ciccone, Giovannino
Abstract : Introduction: The ERAS protocol (Enhanced Recovery After Surgery) is a multimodal pathway aimed to reduce surgical stress and to allow a rapid postoperative recovery. Application of the ERAS protocol to colorectal cancer surgery has been limited to a minority of hospitals in Italy. To promote the systematic adoption of ERAS in the entire regional hospital network in Piemonte an Audit and Feedback approach (A&F) has been adopted together with a cluster randomised trial to estimate the true impact of the protocol on a large, unselected population. Methods: A multicentre stepped wedge cluster randomised trial is designed for comparison between standard perioperative management and the management according to the ERAS protocol. The primary outcome is the length of hospital stay (LOS). Secondary outcomes are: incidence of postoperative complications, time to patients' recovery, control of pain and patients' satisfaction. With an A&F approach the adherence to the ERAS items is monitored through a dedicated area in the study web site. The study includes 28 surgical centres, stratified by activity volume and randomly divided into four groups. Each group is randomly assigned to a different activation period of the ERAS protocol. There are four activation periods, one every 3 months. However, the planned calendar and the total duration of the study have been extended by 6 months due to the COVID-19 pandemic. The expected sample size of about 2200 patients has a high statistical power (98%) to detect a reduction of LOS of 1 day and to estimate clinically meaningful changes in the other endpoints. Ethics and dissemination: The study protocol has been approved by the Ethical Committee of the coordinating centre and by all participating centres. Study results will be timely circulated within the hospital network and published in peer-reviewed journals. Trial registration number: NCT04037787 .